Three Lines Of Defense: A Form Of Reinforcement Of Village Owned Enterprise - Intiyas Utami; Aprina Nugrahesthy Sulistya Hapsari; Yohanes Yakobus Werang Kean; Natasia Alinsari (Jurnal Reviu Akuntansi dan Keuangan, 2022)
This study aims to explore the controls implemented in Village Owned Enterprises (BUMDes) financial management from the perspective of the three lines of defense at BUMDes "KITA" Wologai Tengah Village, Ende, East Nusa Tenggara. This study uses a qualitative descriptive method with sample collection techniques using primary data through FGDs and in-depth interviews with BUMDes management and village government, as well as secondary data through supporting documents. The research data obtained is processed by coding the results of the data collection stages, reduction, verification, and formulation of answers to research problems. The result shows that Three Lines of Defense model adopted by BUMDes “KITA” has not provide an optimal result in every line. This is because of this BUMDes is still new which has been running about three years so they are still focusing on the how to develop the BUMDes. So, they have not considered business continuity too much through risk mapping and control in financial management.  This research has implications for the need for further consideration in using the concept of the three lines of defense for BUMDes, in addition to the need for the role of the central government in optimizing risk management to mitigation of fraud.